The Effectiveness Of Bilingual Teaching In Enhancing Students’ Vocabulary Mastery At SMK Tiara Nusa Borong - Fidestri Riani Murdian Murdian; Anastasia Bawut (CV. AKIRA JAVA BULU, 2026)
This study explores how effective bilingual teaching can be enhancing students vocabulary skills at SMK TIARA NUSA BORONG, specifically focusing on class X ULW 2. To measure the impact of this teaching method, the researcher use pretest and postest design. The data anlysis involve descriptive statistics and more advanced techniques like paired sample t-test and correlation analysis. The result quite promosing. On average scores jumped from 35.00 in pretest up to 73.00 in posttest then the lowest scores significantly improve, rising from 10 to 50. The analysis also show the correlation between pretest and postest with a correlation coefficient of r = .595 and a p-value of .006 , indicating that the chance were statistically significant.